Tensile testing of square structure built with electron beam melting - MUTLU MİTİL, BİLÇEN (CONSEJO SUPERIOR INVESTIGACIONES CIENTIFICAS-CSIC, 2021)
Nowadays, additive manufacturing (AM) makes possible the production of complex metallic parts, and the use of the titanium alloy known as Ti6Al4V with AM has become a common application through the industry. One of the most promising designs for AM is the use of lattice structures that offer lightweight parts with high strength and damping properties. Due to these features, its importance is increasing day by day in sectors requiring high technology such as aerospace. In this study, two different 2D lattice structure specimens having the same lattice density but one with wall thickness, the other one without wall thickness, have been produced with the Electron Beam Melting method and their tensile strength has experimented. Comparing the strain of both specimens, the wall thickness greatly affects the strain values. According to both FEM and tensile tests, the samples with wall thickness demonstrated improved tensile strength behavior. Production was carried out with the same production parameter values. Fracture surfaces are scanned with the Scanning Electron Microscope (SEM).
Keywords: Additive manufacturing; Electron beam melting; Finite element method; Lattice structures; Scanning electron microscope; 2-D square; DIRECT LASER DEPOSITION; MECHANICAL-PROPERTIES; MICROSTRUCTURE; FRACTURE; HOMOGENIZATION